Tumor infiltrating lymphocytes in early breast cancer. (February 2018) - Pruneri, Giancarlo; Vingiani, Andrea; Denkert, Carsten
Abstract: Immunoediting represents a complex and dynamic process involving cancer and immune system cells, composed by three intertwined phases: elimination, equilibrium and escape. A large number of immune cell subtypes are involved, each playing a peculiar role in interacting with cancer cells: cytotoxic CD8 + T cells play a main role in cancer killing by inducing tumor cell death, while FOXP3+ T-regulatory cells represent an immune-inhibitory cell subtype. The evaluation of tumor infiltrating lymphocytes (TILs) in H&E routine samples has been shown to represent a reliable surrogate of the immune anti-tumor activity and a robust independent prognostic biomarker in breast cancer (BC) patients, especially in the Tripe Negative and HER2+ subtypes. The present review addresses the mechanisms of breast cancer immunoediting, its cell complexity and prognostic/predictive relevance, providing evidence that TILs represent one the most promising biomarkers for BC patients. Highlights: TILs in H&E stained slides are a reliable surrogate of anti-tumor immunity. The magnitude and of TIL is variable within and between breast cancer subtypes. TILs and TILs subsets are promising prognostic biomarkers in breast cancer.